The effect of a 12-week exercise training intervention on physical behaviour patterns and perceptions of body image in Black South African women living with overweight and obesity - Phiri, Lindokuhle (Department of Human Biology, 2026)
Background: This thesis aimed to evaluate the effects of a 12-week combined (aerobic and resistance) exercise training intervention on: i) the changes in physical behaviours and ii) body image and self-efficacy. Lastly, iii) this thesis explored the perceptions and experiences of the women after participating in the 12-week combined exercise training intervention. Methods: Forty-five young (18-35 years) apparently healthy Black SA women living with overweight and obesity were randomised into either an exercise (EXE; n=23) or a control group (CON; n=22). The EXE group participated in 12-week aerobic and resistance supervised exercise training (40-60 min/session, 4 days/week), while the control group maintain their usual physical behaviour patterns. Generalized self-efficacy (GSE) questionnaire and Stunkard's silhouettes were used to measure general self-efficacy and perceptions of body image. Participants wore ActiGraph and ActivPAL accelerometers simultaneously for 7 days to quantify physical activity (PA) and sedentary behaviour (SB) at baseline, week 4, 8 and 12, considering all days, exercise days and non-exercise days. Focus group discussions (FGDs) and in-depth interviews (IDIs) were conducted to investigate the participants' perceptions and experiences of the intervention. Results: Thirty-five participants, EXE (n=20) and CON (n=15) completed the intervention. There was a group x time interaction for body weight and CRF, whereby weight decreased by ~1 kg (p= 0.007) and cardiorespiratory fitness (CRF) increased by ~2.7 ml/kg/min (p=0.001) in the EXE group only. Considering only exercise days, moderate-to- vigorous physical activity and total physical activity (%) increased from baseline to weeks 4, 8 and 12 in the EXE group, but did not change in the CON group (p<0.001 for group x time interaction). Daily steps accumulated during the exercise days increased from baseline, (mean ± standard deviation; 9429 ± 4019 steps/day) to week 4 (15050 ± 3167 steps/day; p<0.001), week 8 (14780 ± 4224 steps/day; p<0.001) and week 12 (15695 ± 3550 steps/day; p<0.001), but did not change in the CON group (10131 ± 4561 steps/day). There was a significant decrease in SB (% of awake time) from baseline to week 12 (58.9 ± 9.4% to 48.9 ± 9.1%; p<0.001 for group x time interaction) among the EXE group considering exercise days only. Despite the average measured body mass index of 33.8 ± 2.7 kg/m2 for both groups at baseline, 31.4% of the women classified themselves as normal weight, 65.7% as overweight and only 2.9% as living with obesity. None of the women perceived themselves as living with obesity after the intervention. The Stunkard's silhouettes showed that women from both groups presented with body size discordance, such that at baseline, most participants desired a smaller body size and this did not change in response to the intervention. A significant decline in general self-efficacy was observed in both groups post intervention (p=0.021, time effect), and this did not differ between groups (p=0.801, for group x time interaction). Qualitative findings showed that weight loss (anticipated and actual) and financial remuneration for travelling costs and time (nominal) were reported as motivators for enrolling and staying in the intervention. Improvement in psychological wellbeing (improved mood and self-esteem) and perceived level of self-efficacy were other reported benefits of the intervention. Lack of time, distance to the training venue and limited transport to the training venue were some of the barriers to attending the exercise sessions. Conclusion: To the best of our knowledge, this is the first study in SA to show significant increases in TPA and MVPA, with compensatory reduction in SB in response to combined exercise training among women living with overweight and obesity. A clear indication that the overall changes in the physical behaviour patterns among the exercise group were largely due to the participation in the exercise sessions. Furthermore, the positive changes in physical behaviour patterns and CRF experienced by the exercise group have the potential to improve the cardiometabolic health of this population. In addition, findings from this thesis show promise of the positive impact of exercise on improving psychological wellbeing. Lastly, majority of the women in the study desired to be smaller in body size, suggesting that these women may be receptive to health and weight-loss exercise interventions.